Pendampingan Praktek Shalat Nabi di Desa Kajan Kecamatan Blega Kabupaten Bangkalan - Moh Sholeh; Sama’un Sama’un; Ach. Ghufron (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Assistance in the Practice of the Prophet's Prayer in the village of Kajan, Blega sub-district, Bangkalan district. The problem raised in this community service activity is related to the ability to practice prayer which is very important from the da'wah of Muslims, so learning about how to pray according to the guidance of the Prophet must be conveyed intensely and easily understood by the congregation (local language is allowed). To find alternative solutions to the above, a Prophet's Prayer Practice Assistance was held in Kajan village, Blega sub-district, Bangkalan district. The objectives of this PkM activity are: 1) Relating to the problem of basic abilities regarding the meaning of prayer and its legal basis. 2) Relating to the problem of knowledge of the pillars of prayer along with the conditions for valid prayer. 3) Related to the urgency of the ability to understand things that cancel prayer. 4) Relates to the urgency of the ability to understand the types of obligatory prayers and sunnah prayers. 5) Regarding the urgency of the existence of the companionship and practice of the Prophet's prayer in the village of Kajan Kec. Blega. Based on the agenda of ablution practice activities on Friday night. Can provide knowledge and increase their ability to understand the correct procedure for prayer. Because establishing the correct prayer is a must for every Muslim, so it needs to be trained from an early age. By teaching children from an early age about prayer so that good deeds are instilled in the child's self and soul.